Auditoria de inteligência: uma análise das contribuições da unidade de auditoria interna governamental para a tomada de decisão na Universidade Federal do Rio Grande do Norte - Barros, Ricardo Alexandre Bastos (2022)
The transformations that the governmental internal audit activity has undergone in recent years, due to the need for convergence with good international practices, have brought it closer to consultative audits, such as those of information assets. Therefore, government internal audits focused their efforts on assessment and consulting activities regarding governance, risk management and internal controls. This paradigm shift highlights the need to evaluate information and knowledge management in these units with the aim of improving their informational products. In this sense, an approach that emphasizes the information environment as a whole, with emphasis on information culture, behavior and policy, can contribute to this change insofar as it highlights personal and informational behavior, being concerned not only with offer information, but also in facilitating its effective use, in helping individuals to search for, share, structure and make sense of information. Thus, the objective of this research is to analyze, from the managers' perspective, the contributions of the informational products of UFRN's internal audit to the decisionmaking process. Therefore, it was necessary to characterize UFRN's governmental internal audit as a producer of strategic information; develop a profile of internal auditing and its informational products in the view of UFRN's senior management members; identify the informational needs of the University's senior managers in the decision-making process; verify which factors influence the use of informational products of the audit in this process; and propose informational auditing products to meet such needs. It is, therefore, a social research of the applied and participatory type; also characterized as qualitative; descriptive and explanatory; bibliographic and documentary. It was applied to UFRN's senior management members, who are the main recipients of the work developed by the internal audit unit. Its objectives were achieved by verifying the degree of adherence of the unit's procedures and products to the classical method proposed by Platt (1974); semi-structured interviews with the University's senior management members; and the elaboration of an intervention proposal containing recommendations for informational auditing products aimed at improving the quality of the unit's products, meeting the informational needs of managers and, consequently, improving the provision of services to society. To achieve this purpose, the intelligence audit method proposed by Carvalho (2010) was applied. The adherence of the unit's procedures and products to the classic method proposed by Platt (1974) was confirmed and a profile of the internal audit and its informational products was elaborated in the view of the members of the University's senior management, who consider that the members of the unit of internal audit understand the institution's business and strategy. They also consider that the information produced by the unit is strategic and that their work is relevant to the decision-making process, that the results of the audit work meet their expectations and that the communication of these results is efficient. The informational needs of UFRN's senior management members in the decision-making process were identified, such as the need to keep up to date with the legislation, especially with regard to the internal resolutions of the higher collegiate bodies, and the control of compliance with the goals established in the University's management plan and institutional development plan. Furthermore, it was found that the use of audit informational products in this decision-making process is conditioned to the type of informational demand with which the manager is confronted and that, when there are works carried out by AUDIN on the subject, they are consulted. Finally, a proposal for informational auditing products was formulated to meet the informational needs related to the decision-making process of UFRN's senior management members.